The Effect Of The Adelson Model Using Visual Presentation Methods In Learning The Effectiveness Of The Triple Jump For Students In The Department Of Physical Education And Sports Sciences (Journal of the College of Basic Education, 2024)
Research objectives: Preparing and applying educational units according to the Adelson model using visual presentation methods, and identifying the effect of the Adelson model using visual presentation methods, the triple jump, for the students of the second stage, Department of Physical Education and Sports Sciences. Identifying the effect of the Adelson model through visual presentation methods on the effectiveness of the triple jump for second-year students in the Department of Physical Education and Sports Sciences. Identifying the superior effect of the experimental and control research groups on the effectiveness of the triple jump for second-year students in the Department of Physical Education and Sports Sciences. The researchers used the experimental method by designing two groups, control and experimental. The research population was determined from the third-year students of the Department of Physical Education and Sports Sciences, College of Basic Education, and their number was 59 students, Hall 1, 29 male and female students, and Hall 2, 30 male and female students. After that, the researchers selected the research sample in a systematic random way and determined the composition of each group. 10 students, and then the researchers conducted homogeneity and equivalence for the sample. After that, the researchers carried out the most important research procedures, preparing educational units according to the Adelson model using visual presentation methods. They then proceeded to conduct the pre-test and conduct an experiment for a period of 12 weeks, with one educational unit per week, the time of the educational unit being 90 minutes, and then the post-test was conducted and the researchers relied on Interpreting the results using many statistical methods and tabular comparison, he reached results that led him to many conclusions, the most important of which is the effect of the Adelson model using presentation methods in learning the triple jump. The Adelson model took into account the students’ abilities and their desire for independence. The most important recommendations of the research were - benefiting from the educational units according to Adelson's model, using visual presentation methods, teaches the technical performance of the triple jump event. Emphasis on the application of visual presentation methods to motivate students to learn through excitement and suspense and to get out of learning activities.